Prospection and retrospection in metacommunicative activity (based on the Russian and Belarusian online forums of Belarus) - Bobko, Tatyana V. (Journal of the Belarusian State University. Philology, 2019)
The article examines conditions of actualization and frequency of prospective and retrospective Russian and Belarusian metacommunicative comments. The study is carried out on the material of Russian and Belarusian non-specialized online forums of Belarus, which allows to observe directly the metacommunicative reflection of speakers. It was found that prospective and retrospective orientation of Russian and Belarusian meta-comments depends on metacommunicative and sociolinguistic factors. Purposes of metacommunicative monitoring determine the general properties of Russian and Belarusian metacommunicative prospection and retrospection: correlation with the direction (reflexive and non-reflexive; metalinguistic, metatext, actually metacommunicative) and functional type of metamessage (providing the understanding, organizing, estimating). Prospection, in contrast to retrospection, demonstrates the dependence of relation of the communication language. Main lines of differences are reflected in relation to the linguistic norm, interest in interactivity and evaluation of potential conflict communication.
Keywords: metacommunication; metalanguage; рrospection and retrospection; folk linguistics; Internet communication; language situation